Asma Afsaruddin’s Contextual Hermeneutics of the Discourse on Jihād and Leadership in Islam - Nuryanto; Ahmad Iqbal Annahawan; Oky Akmal Rustandi; Dhiwa Adlani Nahar (UIN Siber Syekh Nurjati Cirebon, 2026)
This article examines Asma Afsaruddin’s historical-contextual interpretive framework for ḥadīths on jihād and Islamic political leadership as a response to the biases of textualist-literalist readings. This qualitative library study focuses on two of Afsaruddin’s principal works: Striving in the Path of God: Jihad and Martyrdom in Islamic Thought (2013) and The First Muslims: History and Memory (2008). The data are analyzed through content analysis and critical discourse analysis in three stages: semantic inference from the texts; tracing asbāb al-wurūd and medieval sociohistorical contexts; and comparing interpretations from the early (formative) and imperial periods. The findings reveal three principal points. First, at the level of semantic analysis, Afsaruddin argues that the term jihād in early traditions carries approximately 70 percent nonmilitary meanings—especially moral and spiritual striving—before narrowing toward a predominantly militaristic sense during the Umayyad and ʿAbbāsid periods. Second, in the field of tafsīr, Afsaruddin documents how medieval jurists’ claims of naskh concerning peace-oriented passages—including their treatment of Q 9:5—contributed to distorted interpretations of ḥadīths on interreligious relations. Third, with regard to leadership, she recovers early egalitarian traditions centered on shūrā that were later displaced by authoritarian ideologies after the era of the Rightly Guided Caliphs. This study contributes to contemporary ḥadīth studies by offering a structured historical-methodological model for distinguishing early normative teachings from medieval political constructions without relying on speculative epistemological claims.